2020
DOI: 10.1001/jamanetworkopen.2019.21610
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Patterns With Testicular Function in Young Danish Men

Abstract: IMPORTANCE Diet may play a role in testicular function, but data on how adherence to different diet patterns influences human testicular function are scarce. OBJECTIVE To determine whether adherence to specific dietary patterns is associated with testicular function in young men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Fifteen peer-reviewed research studies comprised the primary citations used by 34 of the 52 total articles links (Table 4) [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The remaining 18 links did not cite original peer-reviewed scientific studies, or purported study data were not accessible.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen peer-reviewed research studies comprised the primary citations used by 34 of the 52 total articles links (Table 4) [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The remaining 18 links did not cite original peer-reviewed scientific studies, or purported study data were not accessible.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the role of testosterone in affecting sperm maturation and development, our study also found that testosterone-related dietary pattern decreased the SC and percentage of NSM, suggesting a reduction in spermatogenesis. However, a recent study conducted among 2935 Danish men showed reversed results [ 11 ]. The authors reported that men with the highest adherence to the Western pattern had higher testosterone levels compared to men with less adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that men with the highest adherence to the Western pattern had higher testosterone levels compared to men with less adherence. Nevertheless, the FSH and LH levels have remained unchanged regardless of the adherence to the dietary patterns [ 11 ]. In our study, it appears that higher quartiles of the testosterone-related dietary pattern may lead to increased aromatization of testosterone to estradiol ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of emerging pandemics causing city lockdown and health care need for remote regions, tele-medicine will prevail and requires on-line processes of data and analysis connected with off-line point-of-care tests for end users. The Bemaner system is a prime example of this type of implementation, especially for infertility, which is always related to the following aspects: environmental pollution, life style, and diet [ 15 - 17 ], the analysis of big data could contribute much more than traditional case reports in research [ 18 ].…”
Section: Discussionmentioning
confidence: 99%